An Economic Justification of Protectionism: Comment - Koo, Anthony Y. C. (Quarterly Journal of Economics, 1961)
Journal Article An Economic Justification of Protectionism: Comment Get access Anthony Y. C. Koo Anthony Y. C. Koo Michigan State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 1, February 1961, Pages 133–144, https://doi.org/10.2307/1883209 Published: 01 February 1961